O clã dos Canguçus no Brejo do Campo Sêco: fazenda de criação, guerra de famílias e poder no alto sertão da Bahia do século XIX - Lima, Rui Marcos Moura (2024)
The present thesis aimed to carry out a detailed analysis of the Canguçus clan in its agropastoral activity at Fazenda Brejo do Campo Sêco. In this way, a historiographical exercise was carried out that promotes the intersection between two areas of knowledge: Family History and Agrarian History. With regard to the geographical borders, we are transported to the remote hinterlands of the Baiana Province, more specifically to the Alto Sertão, in a period in which the effort of the Portuguese Crown to colonize and populate the most distant regions of the colonial interior was still being glimpsed. For this purpose, we analyze the deed of purchase and sale of the farm, dated 1749, as the initial point of temporal reference. By acknowledging land ownership and exploitation as central elements in our analyses, we consider the individuals who formed the first family to acquire and take control of the breeding farm. In this sense, we highlight the relevance of the binomial composed of Micaela Maria de Jesus and Ana Francisca da Silva, respectively mother and daughter. While the former conceived and executed a plan to acquire such lands, the latter outlived the successive generations of men who were at the head of the administration of the farm and, over the course of approximately one hundred years, was involved in the daily activities of the enterprise, not only in the private sphere, but also playing an active role in the administrative management of the property. We follow the domain successions of this farm, seeing up close the daily life, the practice of cattle raising and agriculture based on the labor of enslaved men and women, as well as the transactions carried out in the private sphere, often conflictive. At the end of the research, we addressed a clash between families, led by the Canguçus. This conflict began in 1844 with the kidnapping and “defloration” of Pórcia Carolina da Silva Castro, carried out by Leolino Pinheiro Canguçu, son of the patriarch, Inocêncio José Pinheiro Canguçu. The relentless pursuit of revenge in the name of outraged honor was analyzed as a result of this episode. The Castros, seeking reparation for their tarnished honor, allied themselves with the Mouras – former rivals of the Canguçus – which triggered a sequence of violent acts and crimes that culminated in Leolino's death in 1846. Our final milestone will be the year 1851, when Inocêncio Pinheiro Canguçu will be tried for the family's crimes. We were instigated to investigate the dimensions of the power of this family and to seek to understand what underpinned such domination in the region. We start from the premise that the main mainstay of the Canguçus' power resided in the possession of the land. At the end of the research, we confirmed this hypothesis and identified other mechanisms for obtaining and maintaining power throughout the family trajectory. Among the various documents consulted, it is worth mentioning that we found two singular manuscripts: the “Livro de Razão” and the “Livro de Gado”, used in the administration of the farm. We highlight the relevance of the preservation and rarity of these documents, which recorded the activities of three generations of the Brejo do Campo Sêco Farm throughout the colonial and imperial periods. Such a discovery stands out for its importance, since it is unusual to find a complete document covering an extensive time period with sequential information about a specific historical reality within the historiographical field.